Overview of Patagonian Red Octopus (Enteroctopus megalocyathus) Fisheries in Chilean Regions and Their Food Safety Aspects - Alessandro Truant; Federica Giacometti; Jorge Hernández; Viviana Espinoza; Ana Farías; Iker Uriarte; Cecilia Godoy; Riccardo Miotti Scapin; Leonardo Alberghini; Paolo Catellani; Valerio Giaccone (Animals)
Artisanal fisheries in southern Chile rely heavily on the Patagonian red octopus (Enteroctopus megalocyathus) as a valuable resource, contributing significantly to local economies. This octopus species accounts for 25–40% of Chilean octopus landings. It is a merobenthic species, characterized by a semelparous life cycle and a long brooding period, and it is distributed along the Pacific and Atlantic coasts of the southern tip of South America, inhabiting holes and crevices in rocky substrates. However, this fishery faces critical challenges to both its ecological sustainability and the food safety of octopus products. The primary fishing method, using hooks, poses a risk to reproductive capacity as it can capture brooding females. Food safety concerns arise from microbial contamination during pre- and post-harvest handling, bioaccumulation of toxins from algal blooms, and the presence of heavy metals in the marine environment. While evisceration effectively reduces the risk of consuming toxins and heavy metals, inadequate hygiene practices and insufficient ice usage throughout the production chain represent significant food safety risks. Chilean fishing Law No. 18892/1989 defines artisanal fishing and establishes territorial use rights in fisheries (TURFs) to promote sustainable extraction of benthic resources. Integrating training programs on post-harvest handling, hygiene practices, and food safety measures into the TURFs framework, along with targeted investments in infrastructure and technical assistance, is crucial to ensure the long-term sustainability of the E. megalocyathus fishery, protect consumer health, and maintain the economic viability and environmental sustainability of this vital resource for local communities.